SAT-590 A Case Report: Successful Treatment of Thyroid Storm with Plasmapheresis - Schapira Wajman, Delane (J Endocr Soc, 2019)
Background: The thyroid storm is a rare disorder characterized by multisystem involvement and high mortality rates. A high index of suspicion should be maintained in patients with thyrotoxicosis associated with evidence of systemic decompensation. Case Presentation: A 25 year old male was referred to an endocrine clinic with the diagnose of Graves disease, complained about 34kg weight loss, goiter, diarrhea, palpitation and exophthalmia, his hormonal profile showed TSH <0.05 uUI/mL (0.4-5.8), T4l >7.77 ng/dl (0.7-1.8), TRAb 25.2 UI/L, T3>651,0 ng/dl; Methimazole 20mg/day, and Propanolol 120mg/day were introduced at that appointment. After a month the patient was admitted at Santa Casa de São Paulo hospital as a result of orquiepididymitis and jaundice. He evolved 48hs after the admission with respiratory insufficiency, fever and tachycardia. Propylthiouracil 200mg 4/4hs, Lugol 8/8hs, dexamethasone, Tazocin, Meropenem, Vancomicine were introduced by the internal medicine team. The laboratory profile showed: total bilirubin 11.4, direct 10.4, RNI 2.06, AST 40, ALT 46, hemoglobin 10.7, hematocrit 33.4, leucocytes 7800 (86,7% neutrophils), plaques 128.000. Transthoracic echocardiogram revealed diffuse hypokinemia, mainly antero-septal, FE=38%, moderated left ventricle eccentric hypertrophy. After 48hs the endocrine team discontinued thionamide drugs, lithium and plasmapheresis was indicated. The patient did 3 session of plasmapheresis, the day after the first section he was extubated, and his hormonal scan revealed TSH 0.01 (0.4-5.8), T4l 1.04 (0.7-1.8), at that day. After recovering from the infection a total thyroidectomy was performed, and levothyroxine 1.0mcg/kg/day was introduced. The patient had post-operative hypoparathyroidism and is takin calcitriol, calcium carbonate and cholecalciferol. Conclusion: A multimodality treatment approach should be used. Therapeutic plasma exchange (TPE) is a potential therapeutic option for thyroid storm, but its indication is not well established. The literature contains few reported cases and no clear guidelines about indication criteria and best time to start. When there are threatening symptoms, TPE should be done early, without waiting for the efficiency of conventional treatment. It’s effect can be explained by the rapid decline of plasma hormones and antibodies responsible for Graves’ disease. It is a relatively safe therapy, although it has a high cost. Monitoring the thyroid hormones is interesting, but clinical improvements are often dissociated from the hormonal levels and must be mainly judged on the patient’s condition.